Indirect impacts of the COVID-19 pandemic at two tertiary neonatal units in Zimbabwe and Malawi: an interrupted time series analysis - Michelle Heys; Caroline Crehan; Emma Wilson; Felicity Fitzgerald; Mario Cortina Borja; Msandeni Chiume; Samuel R Neal; Hannah Gannon; Gwen Chimhini; Simbarashe Chimhuya; Tim Hull-Bailey; Tarisai Chiyaka; et al. (BMJ Open)
Objectives To examine indirect impacts of the COVID-19 pandemic on neonatal care in low-income and middle-income countries.Design Interrupted time series analysis.Setting Two tertiary neonatal units in Harare, Zimbabwe and Lilongwe, Malawi.Participants We included a total of 6800 neonates who were admitted to either neonatal unit from 1 June 2019 to 25 September 2020 (Zimbabwe: 3450; Malawi: 3350). We applied no specific exclusion criteria.Interventions The first cases of COVID-19 in each country (Zimbabwe: 20 March 2020; Malawi: 3 April 2020).Primary outcome measures Changes in the number of admissions, gestational age and birth weight, source of admission referrals, prevalence of neonatal encephalopathy, and overall mortality before and after the first cases of COVID-19.Results Admission numbers in Zimbabwe did not initially change after the first case of COVID-19 but fell by 48% during a nurses’ strike (relative risk (RR) 0.52, 95% CI 0.41 to 0.66, p<0.001). In Malawi, admissions dropped by 42% soon after the first case of COVID-19 (RR 0.58, 95% CI 0.48 to 0.70, p<0.001). In Malawi, gestational age and birth weight decreased slightly by around 1 week (beta −1.4, 95% CI −1.62 to −0.65, p<0.001) and 300 g (beta −299.9, 95% CI −412.3 to −187.5, p<0.001) and outside referrals dropped by 28% (RR 0.72, 95% CI 0.61 to 0.85, p<0.001). No changes in these outcomes were found in Zimbabwe and no significant changes in the prevalence of neonatal encephalopathy or mortality were found at either site (p>0.05).Conclusions The indirect impacts of COVID-19 are context-specific. While our study provides vital evidence to inform health providers and policy-makers, national data are required to ascertain the true impacts of the pandemic on newborn health.